(untitled) (Journal of the College of Basic Education, 2022)
The research aims identify extent to which teachers of the mathematical of departments in the colleges of basic education possess university teaching skills. The researcher prepared a questionnaire for university teaching skills, we have produced questionnaire of the validity and the reliability, The questionnaire becomes final form is composed of (56) items divided in to(4)fields : (planning for teaching courses skill, implementing teaching skill, evaluating students’ learning and providing feedback skill, communication and communication between Students skill), and Then the questionnaire was applied on the research sample consists of(43) teachers from the departments of mathematics in the of basic education colleges from Al-Mustansiriya University, Maysan University and Diyala University. ) To achieve the aim of the research, use the following: statistical means, standard deviations, Independent-samples (t-test), Research results showed to:- 1- There are (62) skills The Mathematics Department teacher possesses from university teaching skills. 2-There are statistically significant differences at the level of significance (0.05) in the mean the estimation of the mathematics of department teachers in the degree of their possession of teaching skills due to the variable scientific qualification. 3-There are no statistically significant differences at the level of significance (0.05) in the mean estimation of the mathematics of department teachers in the degree of their possession of teaching skills due to the variables of years of experience and the college from which they graduated. In the light of the results of the research, the researcher presented some recommendations and suggestions for the purpose of doing research and subsequent studies.